Tinjauan Literatur Kompetensi Kewirausahaan Pada Usaha Kecil Menengah (UKM) - Farhan Maulana; Muhamad Rizal; Ria Arifianti (Majalah Bisnis & IPTEK, 2020)
Entrepreneurial competence is knowledge, attitudes and skills that are connected to one another, which is needed by entrepreneurs to be trained and developed in order to be able to produce the best performance in managing their business. In the activities of Small and Medium Enterprises (UKM), this entrepreneurial competence is also very necessary. Entrepreneurial competence is also rarely discussed, especially in SMEs. So, we discuss the classification, identification of several scientific publications and analyze the literature to create a detailed understanding of the entrepreneurial competence field in SMEs. We use the Systematic Mapping Study (SMS) method to examine various articles on entrepreneurial competence in SMEs based on the focus and type of research over time. The results show the categories and quantification of entrepreneurial competency studies into various dimensions, as well as an overview of current research topics and trends in entrepreneurial competence in SMEs.